The Influence Of The Threat Of Technological Innovation On Student Job Insecurity: The Mediating Role Of Digital Literacy, Personal Innovation, And Technological Innovation - Ratnawati, Shinta; Paska, Yesica Apriliana; Sadewo, Satrio Tegar; Ernawati, Nimas Jimi; Anggraeni, Dewi (UNIVERSITAS PAKUAN, 2025)
The rapid development of technology raises concerns about the future of employment, especially for students who are preparing to enter the world of work. This study was conducted to examine the effect of the threat of technological innovation on the level of career concerns (job insecurity) of students, as well as to analyse the mediating role of digital literacy, personal innovation, and technological innovation. This research uses a quantitative approach with a quasi experiment method using a pretest-posttest control group design. The research population was the final year students of Tidar University, with sampling using random sampling technique to obtain 100 respondents. The sample was divided into two groups, namely the experimental group that received treatment in the form of materials, videos, and articles on the impact of technological disruption, and the control group without treatment. The research was conducted for three months from March to May 2025. The results showed that the threat of technological innovation has a positive effect on student job insecurity, both directly and through the mediating role of digital literacy, personal innovation, and technological innovation. This finding implies that strengthening technological competence without mental readiness can increase career anxiety. Therefore, educational institutions are expected to not only improve digital literacy, but also develop programmes to strengthen students' psychological adaptation in the face of industry changes.